Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Elektronika Dasar Dalam Materi Hukum Ohm Dengan Menggunakan Metode Demonstrasi Di Kelas X Smk Muhammadiyah 1 Banda Aceh - Zuyadi, Zuyadi; Silahuddin, Silahuddin; Anna Lastya, Hari (PTE FTK UIN Ar-Raniry, 2018)
The implementation of demonstration methods in productive learning is very influential on the level of student learning success in SMK. The results of observation indicated that many student learning outcomes of SMK were below average. This was caused by teachers who did not apply the demonstration method in the lesson, so it affect their learning ability. This study aims to determine the level of students learning success at class X SMK Muhammadiyah 1 Banda Aceh by applying the methods of demonstration on Basic Electronics subjects. This research is a quantitative research using pre- experiment design method: one-group pretest-posttest design. Data were collected through pretest, posttest and questionnaires. Then the data was processed by using t-test. The results of the study revealed that there are differences in learning outcomes of students of class X SMK Muhammadiyah 1 Banda Aceh between after and before applied methods of demonstration. This can be seen from the average score of student achievement achieved on pretest < posttest (74.5 < 80.5). After analyzed by using the t- test formula obtained t-count = 1.96. While t-table obtained by using dk = n-1, dk = 10-1 = 9 at a significant level of 5%, ie 0.251. Base on the initial hypothesis of this study, it indicated that, if tcount > ttable (1,96> 0,521), Ha is accepted. Thus it can be concluded that the implementation of demonstration methods can improve student learning outcomes of class X SMK Muhammadiyah 1 Banda Aceh.